IMPLEMENTATION OF BLENDED LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES ON THE CONCEPT OF REACTION RATE - Zulhera Aprilia; Rusman Rusman; Ratu Fazlia Indah Rahmayani (FKIP USK, 2022)
This study aims to observe activities, learning outcomes and describe students' responses to blended learning on the concept of reaction rate. This is a descriptive research with a qualitative approach. The research subjects were 29 USK Chemistry Education students who programmed the Basic Chemistry II course in class 02 of the 2018/2019 academic year. Data were collected through tests, observations and questionnaires. The instruments used in this study were learning outcomes test questions, student activity observation sheets and student response questionnaires. The results of observation of student activities are categorized as very good, learning outcomes are included in the good category with a score of 73.7. The application of blended learning received positive responses (71.7%). Based on the results of the study, it was concluded that the application of blended learning on the reaction rate material had a positive impact on learning activities and outcomes and received good responses from students.